Natural abundance isotope techniques offer a key to better deciphering the impact of microplastics on the nitrogen cycle - Chen, Yangjun; Zhang, Xingzhou; Yang, Yuanyuan; Chen, Min (Frontiers in Marine Science, 2025)
As human activities intensify, ecosystems are constantly being polluted by microplastics, which may change the microbe-driven nitrogen cycling and associated nitrous oxide emissions therein. However, the exact impact of microplastics on specific nitrogen cycling processes remains to be clarified, limiting accurate assessments of nitrous oxide production. Additionally, a gap in our understanding of the isotopic dynamics of nitrogen cycling under the impact of microplastics restricts deeper insights into nitrogen cycling in microplastic-polluted environments. Accordingly, this study represents the first integration of natural abundance isotope techniques with microcosm experiments involving various microplastics, offering a novel approach for detailed investigation into the impacts of microplastics on the nitrogen cycle dynamics and their potential role in regulating nitrous oxide production. Our results suggest that microplastics of different sizes (0.02 mm, 0.1 mm, and 1 mm) and polymer types (polypropylene, polyvinyl chloride, polyamide, and polyethylene) impact both nitrite production and consumption, highlighting the important role of size in these processes. Particularly, nitrite dual isotopic signatures help identify specific nitrogen cycling processes impacted by microplastics. More importantly, isotopic evidence indicates that nitrite may be lost from the environment primarily by reduction to gaseous products nitrous oxide or dinitrogen in polyethylene and polyvinyl chloride, especially the largest-size polyamide treatments. Conversely, polypropylene treatment, especially at large sizes, may promote nitrite oxidation, thus retaining more nitrogen within the environment. Our findings offer a new paradigm for the comprehensive assessment of the impact of microplastics on the nitrogen cycle and highlight the importance of considering microplastics when assessing greenhouse gas emissions, especially in the context of increasing microplastic pollution.